Australia and the Insular Imagination: Beaches, Borders, Boats, and Bodies - Perera, Suvendrini (Palgrave Macmillan, 2009)
Most studies of Australia begin with the "the island-continent". The surrounding oceans are little more than a backdrop for the dramas that occur on dry land. This is the first book to turn its attention to the oceans and coastlines that make and remake the limits of Australia through events such as the arrival of asylum seekers' boats, the Indian Ocean tsunami, the Bali bombings and maritime peacekeeping missions in the Pacific. Against the imperatives of war, security, aid and disaster, various configurations of bodies, boats, borders and beaches testify to the power and the limits of Australia's insular illusion.